Renal Transplantation in Patients with Cystinosis – A Case Series - Yashwanth Raj Thiagarajan; Dinesh Kannabhiran; Kanakaraj Arumugham; Rajan Ravichandran (Indian Journal of Transplantation)
Cystinosis is a rare autosomal recessive lysosomal storage disorder causing intracellular accumulation of cystine in different organs, leading to several organ dysfunctions. Renal involvement is the most serious manifestation of cystinosis leading to end-stage kidney disease (ESKD). Here, we report the outcomes of four patients with cystinosis who underwent kidney transplantation. All the patients were young males. Renal manifestation included Fanconi syndrome and progressive decline in glomerular filtration rate (GFR). One of the patients had nephrotic syndrome with focal segmental glomerulosclerosis. The median age at ESKD was 10 years. Post-transplant, all patients were maintained on tacrolimus-based triple immunosuppression. All patients received cysteamine therapy. The median follow-up duration was 7.5 years. All patients maintained excellent graft function during follow-up except one. The median estimated GFR was 92.6 mL/min/1.73 m2. One patient lost the graft 6 years after transplant due to T-cell-mediated rejection. Kidney transplantation can be safely performed in patients with cystinosis with good long-term outcomes. This is the first case series regarding cystinosis patients who received kidney transplantation from India.